Analisis Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Umum Syariah Di Indonesia Periode 2016-2020 - Harumni Puspa Anuraga; Rafidah; Lidya Anggraeni (Jurnal Publikasi Ilmu Manajemen, 2023)
The purpose of this study is to examine and analyze the effect of Inflation, Non Performing Financing (NPF) on Operational Costs on Operating Income (BOPO) on the profitability of Islamic Commercial Bank in Indonesia. Profitability in this case is indicated by Return On Assets (ROA). The sample in this study was determined using the purposive sampling method, namely the technique of determining the sample with certain considerations. with a number of samples that meet the criteria of seven Islamic Commercial Banks in Indonesia with an observation period from 2016 to 2020. The analysis technique used in this study uses panel data regression with the aim of obtaining a comprehensive picture of the relationship between variables. Based on the results of this study, it shows that partially Inflation has a significant effect on Return On Assets (ROA), Non Performing Financing has no significant effect on Return On Assets (ROA) and Operational Costs on Operating Income (BOPO) has a significant effect on Return On Assets (ROA). Meanwhile, simultaneously Inflation, Non Performing Financing (NPF) and Operational Costs on Operating Income (BOPO) have a significant effect on Return On Assets (ROA).